The Effect of Story Completion Technique Toward Student’s Speaking Skill by using WhatsApp at the Second Grade of SMAN 1 SALO - Silvia Putri Perdana; Wida Rianti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2021)
This research aims to find out whether there is an effect on using Story completion technique towards the students’ speaking skill in online class, in academic year 2019/2020. This research is quasi-experimental research that carried out at first grade students of SMA N 1 SALO. In taking the sample, the researcher used cluster sampling technique. It involved 43 students of two classes, XI IPA 1 as experimental class and XI IPA 2 as control class. Each class consisted of 21 students and 22 students. The experimental class was taught by using Story completion technique while control class was taught by using teacher’s method. The data were analyzed by using T-test formula. Based on the result findings, it can be concluded that the use of Story completion technique in teaching speaking skill in online class is effective. Therefore, it is recommended that Story completion can be implemented as one of the effective teaching technique for the teacher to teach speaking skill and for the future researcher can use the same kind of the research with different sample and condition.